2008
DOI: 10.1172/jci32638
|View full text |Cite
|
Sign up to set email alerts
|

Targeted mutation of mouse skeletal muscle sodium channel produces myotonia and potassium-sensitive weakness

Abstract: Hyperkalemic periodic paralysis (HyperKPP) produces myotonia and attacks of muscle weakness triggered by rest after exercise or by K + ingestion. We introduced a missense substitution corresponding to a human familial HyperKPP mutation (Met1592Val) into the mouse gene encoding the skeletal muscle voltage-gated Na + channel Na V 1.4. Mice heterozygous for this mutation exhibited prominent myotonia at rest and muscle fibertype switching to a more oxidative phenotype compared with controls. Isolated mutant extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
93
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(106 citation statements)
references
References 60 publications
12
93
0
1
Order By: Relevance
“…These changes were present before any spontaneous episodes of paralysis had been observed. Furthermore, they were shown to increase with age in the heterozygotes while muscle force generation declined (Hayward et al, 2008). These findings support the clinical observations that myopathy increases with age (Links et al, 1990;Plassart et al, 1994) and that it may be independent of paralytic attacks in the periodic paralyses (Buruma et al, 1978;Links et al, 1990).…”
Section: Mechanisms Of Muscle Degenerationsupporting
confidence: 82%
See 3 more Smart Citations
“…These changes were present before any spontaneous episodes of paralysis had been observed. Furthermore, they were shown to increase with age in the heterozygotes while muscle force generation declined (Hayward et al, 2008). These findings support the clinical observations that myopathy increases with age (Links et al, 1990;Plassart et al, 1994) and that it may be independent of paralytic attacks in the periodic paralyses (Buruma et al, 1978;Links et al, 1990).…”
Section: Mechanisms Of Muscle Degenerationsupporting
confidence: 82%
“…Recently, a mouse model of hyperkalaemic periodic paralysis has been engineered by introducing the murine equivalent of the SCN4A mis-sense mutation M1592V (Hayward et al, 2008). This mutation causes both myotonia and paralysis in humans (Rojas et al, 1991;Kelly et al, 1997) and was demonstrated to produce the same symptoms in the mouse indicating the validity of the model.…”
Section: Mechanisms Of Muscle Degenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, these data also show that R669H +/m mice do not have an increased susceptibility to force reduction in high K + . This distinction is notable because other disease-associated mutations in Na V 1.4 with gain-of-function alterations in channel activity will predispose muscle to attacks of hyperkalemic periodic paralysis (HyperPP), often accompanied with myotonia (22). R669H m/m muscle was more susceptible to a severe loss of force, in either low or high K + .…”
Section: Figurementioning
confidence: 99%